ANALISIS PERAN TUNGKAT BATIN BATANG NILO MONTI RAJA DI SUKU PETALANGAN DESA BETUNG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Saputra, Efriyandi; ', Hambal; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is influenced by the transformation of Tungkat Batin Batang Nilo Monti Raja’s role on Petalangan tribe in Betung which become a social phenomenon in that community. Tungkat Batin Batang Nilo has a role to keep of Tuah, keep of Marwah, Maintaining Dignity customs, determining the rights of indigenous, to protect the rights of indigenous, and foster cousin. In fact, on this time Tungkat Batin Batang Nilo Monti Raja as a leader in his community has no longer do his own duty. The main question in this research is how does the role of Tungkat Batin Batang Nilo Monti Raja on Petalangan tribe in Betung district Pangkalan Kuras, Pelalawan. The purpose of the research is to know the role of Tungkat Batin Batang Nilo Monti Raja in Betung district Pangkalan Kuras, Pelalawan. The population of the research is 57 people. The researcher used qualitative method. The hypothesis in this research is that there is no single role of Tungkat Batin Batang Nilo Monti Raja on Petalangan tribe in Betung district Pangkalan Kuras, Pelalawan. The results of this research indicate there is no maximum role of Tungkat Batin Batang Nilo Monti Raja on Petalangan tribe in Betung district Pangkalan Kuras, Pelalawan. The results of research benchmark that 50.40%, the people answered There are currently no a role of Tungkat Batin Batang Nilo Monti Raja on Petalangan tribe in Betung district Pangkalan Kuras, Pelalawan Key word: Role, Tungkat Batin Batang Nilo Monti Raja, Petalangan Tribe